2010
DOI: 10.1186/1756-9966-29-145
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of mitochondrial pathway in NCTD-induced cytotoxicity in human hepG2 cells

Abstract: BackgroundNorcantharidin, the demethylated analog of cantharidin derived from a traditional Chinese medicine, Mylabris, has been used in the treatment of anti-cancer effects. However, the detailed mechanisms underlying this process are generally unclear. The aim of this study was to investigate the mechanism of NCTD-induced apoptosis in HepG2 cells.MethodsThe cytotoxicity was measured by MTT assay for cellular viability and by flow cytometry. The mitochondrial membrane potential and reactive oxygen species pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 30 publications
4
40
1
1
Order By: Relevance
“…N-hydroxycantharidimide, which is synthesized by cantharidin, has certain curative effects in liver cancer (16). Previous data showed that NCTD could induce cytotoxicity in HepG2 cells by inducing apoptosis (10); therefore, in the present study, we evaluated HepG2 cell apoptosis. The basal apoptotic population of the sham group was 0.3±0.1%.…”
Section: Discussionmentioning
confidence: 99%
“…N-hydroxycantharidimide, which is synthesized by cantharidin, has certain curative effects in liver cancer (16). Previous data showed that NCTD could induce cytotoxicity in HepG2 cells by inducing apoptosis (10); therefore, in the present study, we evaluated HepG2 cell apoptosis. The basal apoptotic population of the sham group was 0.3±0.1%.…”
Section: Discussionmentioning
confidence: 99%
“…In China, norcantharidin as an anti-cancer drug is currently used to treat breast cancer, hepatoma, leukemia, colon cancer, etc. The well-studied mechanisms for the anti-cancer activity of norcantharidin are its activity of inducing apoptosis via regulation of Bcl-2 superfamily member proteins and caspase activities (Chang et al, 2010), interruption of cell cycle arrest at G2/M phase (Liao et al, 2011), and inhibition of cell metastasis by down-regulates MMP-9 expression (Chen et al, 2009b). It was recently reported that mitogen-activated protein kinases (MAPKs) and signal transducers and activators of transcription (STATs) pathways are also involved in norcantharidin-induced apoptogenesis (Yang et al, 2011b).…”
Section: Cantharidin and Cantharidin Derivativesmentioning
confidence: 99%
“…The median disease-free survival following complete resection of the pancreatic tumor and adjuvant chemotherapy with the first line chemotherapeutic agent gemcitabine is 13.4 and 6.9 months, respectively (3)(4)(5)(6). Although camptothecin has a positive effect on arresting pancreatic tumor growth, many unwanted sideeffects limit its clinical application (5,7). All these dismal data highlight an urgent need for new therapeutic agents that could produce better clinical outcomes for this deadly disease.…”
Section: Introductionmentioning
confidence: 99%